Design of a Ship Speed Control System Using Hybrid Propulsion Based on Fuzzy Logic - Aldoko, Fajar Surya Muhammad; Kurniawan, Edi; Amrullah, Romanda Annas; Nurdiansari, Henna; Sandi, Wulan Marlia (Universitas Muhammadiyah Surakarta, 2025)
The maritime transportation sector, especially in archipelagic countries like Indonesia, faces significant challenges in optimising ship speed and fuel efficiency, particularly when using hybrid propulsion systems. This study aims to design a ship speed control system based on fuzzy logic integrated with a hybrid propulsion system (BLDC motor and diesel engine) for a trimaran vessel. The research employed both static and dynamic testing on the system, measuring parameters such as motor RPM, current consumption, voltage, and fuel efficiency across different speed modes (from 4 km/h to 11 km/h). The results showed that the fuzzy logic-based control system notably improved speed stability and fuel efficiency, especially at lower speeds, compared to conventional systems. Additionally, the system effectively adapted to environmental conditions such as waves and currents, optimising power distribution between the BLDC motor and diesel engine. The conclusion emphasises that this fuzzy logic-based control system offers a promising solution to enhance operational efficiency in hybrid propulsion systems for maritime vessels, ensuring reduced fuel consumption and improved environmental sustainability.